Trends in Indonesian Fermented Fish Research (1967–2024): A Bibliometric Analysis Based on Scopus Database - Mutiara Ulfah; Athiefah Fauziyyah; Anis Khairunnisa; Dini Nur Hakiki (Universitas Ahmad Dahlan, 2025)
Indonesia has a variety of fermented fish products. These products are frequently the subject of academic studies, which result in related research publications. This research contributes to identifying research trends in fermented fish products, particularly in Indonesia using bibliometric analysis. The data sources used are scientific documents published in Scopus. The data were processed in Excel and VOSviewer for data mapping. A total of 83 relevant publications on Indonesian fermented fish were obtained, with the largest output from Indonesia, namely 73 publications. The collected publications published from 1967 to 2024 include 53 articles, 21 conference papers, 4 book chapters, 3 reviews, and 2 books. Data were retrieved in August 2024 using four search strings, i.e, “Fermented Fish AND Indonesia”, “Indonesian Fermented AND Fish”, “Fish Fermentation AND Indonesia”, and “Fermented Seafood AND Indonesia”. The main fermented fish products discussed are terasi (13 publications), bakasang (8 publications), budu (8 publications), peda (6 publications), bekasam (11 publications), jambal (3 publications), rusip (4 publications), chao (4 publications), wadi (3 publications), and inasua (5 publications). The current trend in Indonesian fermented fish focuses on three main areas: microbial diversity and the role of lactic acid bacteria; chemical characteristics and nutritional value; and food safety of fermented fish products. Further research has the potential to develop starter cultures, identify the bioactive compounds, assess food safety, and standardize the fermentation process to maintain product quality.